Analysis of Judges' Decisions in Imposing Laws Against Perpetrators of Fisheries Crimes (Case Study of North Jakarta District Court Decision Number 1/Pid.Sus-PRK/2021/PN Jkt.Utr) - Munazzir, Munazzir; Herli, Dadang; Juwita, Juwita (Jurnal Indonesia Sosial Sains, 2025)
The abundant fishery resources in Indonesia's waters have attracted both domestic and foreign parties, leading to illegal fishing activities. Despite various enforcement efforts, illegal fishing and the lack of a fishing business license continue to occur. Perpetrators of fishery crimes face legal penalties according to their offenses. Court decisions, such as the District Court of North Jakarta ruling No. 1/Pid.Sus-Prk/2021/PN. Jkt.Utr, result from examining the case based on the applicable charges. The research questions are: 1) How is the law applied to perpetrators of fisheries crimes? 2) How does the judge's ruling apply penalties to perpetrators of fisheries crimes based on the ruling No. 1/Pid.Sus-PRK/2021/PN Jkt.Utr? This research uses a normative legal approach to find relevant legal rules, principles, and doctrines. The findings reveal that penalties for illegal fishing are regulated under Articles 84 to 104 of Law No. 45 of 2009 on Fisheries, including the sinking of foreign ships caught fishing without permission in Indonesia's waters. The judge's decision involves legal considerations and principles of justice.